Molecular dynamics study of imidazolium ionic liquids and molecular solvents: insights into microstructure and transport phenomena - Dmytro Dudariev; Yaroslav Kolesnik; Abdenacer Idrissi; Oleg Kalugin (Вісник Харківського національного університету: Серія xімія)
Binary mixtures composed of room-temperature ionic liquids and aprotic dipolar solvents are widely used in the modern electrochemistry. While these systems exhibit maximum electroconductivity and other changes in diluted solutions, as confirmed by NMR and vibrational spectroscopic data, there is currently no theory that can fully explain these phenomena. In current work twelve mixtures of ionic liquids (ILs), in particular 1-butyl-3-methylimdazolium (C4mim+) with tetrafluoroborate (BF4-), hexafluorophosphate (PF6-), trifluoromethanesulfonate (TFO-) and bis(trifluoromethane)sulfonimide (TFSI-) with molecular solvents such as acetonitrile (AN), propylene carbonate (PC) or gamma butyrolactone (γ-BL) were studied by the molecular dynamics simulation technique. The local structure of the mixtures was studied in the framework of radial distribution functions (RDFs) and running coordination numbers (RCNs) that showed the particular behavior in AN and TFSI- systems. For TFSI- system the presence of two peaks on the RDFs with similar intensities were observed. The mutual arrangement of cation and anion corresponding to observed on the RDFs interatomic distances were investigated: they represent the position when the nitrogen atom of the anion is close to the imidazolium ring and when nitrogen atom of TFSI- not directly interacting with the ring, but instead the oxygen atoms do. The cation-anion coordination numbers changed for mixtures with AN from ~1.2 to ~3.6, for PC – from 0.6 to 3.0 and for γ-BL – from 0.8 to 3.1 with the increasing mole fraction of the ILs. Also, the association analysis was conducted using two different distance criteria. The results showed the formation of large clusters at approximately 0.15, 0.20, and 0.25 IL mole fractions for AN, PC, and γ-BL, respectively, based on the first criterion. However, this criterion tends to overestimate the extent of aggregation. In contrast, the second, stricter criterion indicates that the formation of large aggregates begins at IL mole fractions similar to where the experimental conductivity curves reach their maximum. To analyze the transport properties the diffusion coefficients of all the components and shear viscosity for all binary mixtures were obtained. The diffusion coefficients show good agreement with experimental data.